Unveiling the regulatory mechanism of poly-γ-glutamic acid on soil characteristics under drought stress through integrated metagenomics and metabolomics analysis - Hong, Li; Wei, Li; Fanglan, Ge; Jiao, Li; Shiheng, Tu; Hong, Yang; Yao, Ren; Xinyue, Gong; Can, Yao (Frontiers in Microbiology, 2024)
It is of utmost importance to understand the characteristics and regulatory mechanisms of soil in order to optimize soil management and enhance crop yield. Poly-γ-glutamic acid (γ-PGA), a stressresistant amino acid polymer, plays a crucial role in plant drought stress resistance. However, little is known about the effects of γ-PGA on soil characteristics during drought treatments. In this study, the effects of different forms of γ-PGA on soil texture and basic physical and chemical properties under short-term drought conditions were investigated. Furthermore, the impact of γ-PGA on the microbial community and metabolic function of maize was analyzed. Under drought conditions, the introduction of γ-PGA into the soil resulted in notable improvements in the mechanical composition ratio and infiltration capacity of the soil. Concurrently, this led to a reduction in soil bulk density and improved soil organic matter content and fertility. Additionally, metagenomic analysis revealed that under drought conditions, the incorporation of γ-PGA into the soil enhanced the soil microbiota structure. This shift led to the predominance of bacteria that are crucial for carbon, nitrogen, and phosphorus cycles in the soil. Metabolomics analysis revealed that under drought treatment, γ-PGA affected soil metabolic patterns, with a particular focus on alterations in amino acid and vitamin metabolism pathways. Correlation analysis between the soil metagenome and metabolites showed that microorganisms played a significant role in metabolite accumulation. These results demonstrated that γ-PGA could improve soil characteristics under drought conditions and play an important role in soil microorganisms and microbial metabolism, providing further insights into the changes in soil characteristics under drought conditions.